'Playing Cold War politics': the cold war in Anglo-Kenyan relations in the 1960s. Issue 1 (2nd January 2018) - Cullen, Poppy
Abstract: Kenya has rarely been considered a major Cold War battleground, becoming linked with Britain and the Western side, even whilst being publicly committed to non-alignment and African Socialism. Nonetheless, the Cold War offered opportunities for Kenya's newly independent leaders. It was utilised in factional political debates between Tom Mboya and Oginga Odinga. In the late 1960s, leading Kenyans around President Jomo Kenyatta used Cold War rhetoric and rivalries to bargain to their advantage with the British over arms sales. British policy-makers offered concessions as they worked to build and then maintain their position as Kenya's closest foreign partner.